IMPLEMENTASI BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA GURU PADA SLBN 1 KOTA BLITAR - Eko Wibowo; Abd Aziz; Nur Efendi (As-Sulthan Journal of Education, 2026)
The quality of teacher performance is greatly influenced by the school's organizational culture, which can both motivate and hinder productivity. Therefore, creating a positive work environment is crucial in optimizing the dedication and work results of educators. The purpose of this study is to determine whether the implementation of an organizational culture at SLBN 1 Kota Blitar, based on the values ​​of discipline, integrity, respect, and collaboration, has been proven effective in boosting teaching quality. Through consistent internalization of these collective values, the school environment has succeeded in creating higher-quality work standards for all educators. This study used observation, interview, and documentation study methods involving the Principal and teachers and analyzed through data reduction, data presentation and conclusions. The findings of this study revealed that: 1) teacher effectiveness can be accelerated through discipline enforcement. 2) organizational culture planning that focuses on professional development. 3) Creating a solid atmosphere of learning and collaboration is a strategic step to build a more productive and organized educational environment. Ultimately, the success of internalizing these normative values ​​depends heavily on the collective commitment of all school elements to maintain the stability and quality of the institution. The effective implementation of organizational culture at SLBN Kota Blitar has been proven to significantly boost teacher performance. This success confirms that strengthening organizational values ​​is a crucial instrument in efforts to improve instructional quality and student achievement.